2019
DOI: 10.1371/journal.pntd.0007311
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of Brucella species from Zimbabwe

Abstract: Brucella abortus and B . melitensis have been reported in several studies in animals in Zimbabwe but the extent of the disease remains poorly known. Thus, characterizing the circulating strains is a critical first step in understanding brucellosis in the country. In this study we used an array of molecular assays including AMOS-PCR, Bruce-ladder, multiple locus variable number tandem repeats analysis (MLVA) and single nucleotide polymorphisms from whole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 53 publications
0
20
0
Order By: Relevance
“…strains were isolated from seven areas of the examined region. It was important to follow up on the control strategies and implement prevention measures for the identification and typing of Brucella isolates [27]. Subsequently, these strains were identified and typed using classical biotyping methods and molecular schedules.…”
Section: Discussionmentioning
confidence: 99%
“…strains were isolated from seven areas of the examined region. It was important to follow up on the control strategies and implement prevention measures for the identification and typing of Brucella isolates [27]. Subsequently, these strains were identified and typed using classical biotyping methods and molecular schedules.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple-locus variable-number tandem-repeat analysis (MLVA) has high power to discriminate closely related strains and can be used for tracing infections [15], achieves result largely in agreement with WGS-SNP-based typing [16]. In addition, its low cost and fast results allow its use as a routine first-line assay [17]. Ma et al [18] reported that the Brucella strain in Qinghai was different from strains in other regions of the world, possibly owing to the unique geography, such as the high altitude, of the QTP.…”
Section: Introductionmentioning
confidence: 94%
“…Minimum spanning trees (MST) were constructed based on MLVA-11 (Table S2) and MLVA-16 (Table S3) data using BioNumerics 7.6 to investigate the geographic origin and genetic relatedness of strains. Phylogenetic analysis of representative strains (Table S4) was performed based on WGS-SNP using the maximum parsimony method [17], B. abortus bv.1 str. 9-941 used as the outgroup strain.…”
Section: Dna Preparation Genotyping and Data Analysismentioning
confidence: 99%
“…In Hainan Province, which is located at the southernmost part of China, there were no historically reported brucellosis cases, and only one human brucellosis case was reported in Danzhou in 1985, brucellosis cases significantly increased in 2017 between humans (Wang et al, 2019), but the available information on the extent of the disease and relatedness among strains is unknown. Characterizing the circulating strains is a critical sector in understanding brucellosis in the epidemic area (Ledwaba et al, 2019). Accurate discrimination relatedness among strains with the MLVA assay is necessary to determine the source, origin, and geographical spread of infection (Whatmore et al, 2016).…”
Section: Introductionmentioning
confidence: 99%